2012
DOI: 10.1055/s-0032-1316316
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Muscularity in Throwers

Abstract: This study aimed to examine and compare the trunk muscularity of track and field throwers and non-athletes, and its predictive value to the physical performance of the athletes. Using a magnetic resonance imaging method, the skeletal muscle volume (SMV) of the trunk (SMV(trunk)) was determined in 19 strength trained athletes and 18 non-athletes. Also, the SMV of upper, middle and lower regions of the trunk was calculated in every 33% of the trunk length. For the athletes, the maximum weight (1RM) of squat, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Nonetheless, our findings explain between 49% and 72% of the variance in the relationship between CSA and peak torque, which could have been improved by considering PCSA as a more accurate structural determinant of muscle strength. However, given that the reliability of the assessment of fascicle pennation angle of trunk muscles in vivo is not established in the literature, anatomical CSA can be considered as a reasonable alternative of muscle volume evaluation (Kubo et al, 2011;Tanaka et al, 2013). Our correlations could also be affected by the numerous synergist muscles potentially contributing to trunk extensor and flexor torque output.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Nonetheless, our findings explain between 49% and 72% of the variance in the relationship between CSA and peak torque, which could have been improved by considering PCSA as a more accurate structural determinant of muscle strength. However, given that the reliability of the assessment of fascicle pennation angle of trunk muscles in vivo is not established in the literature, anatomical CSA can be considered as a reasonable alternative of muscle volume evaluation (Kubo et al, 2011;Tanaka et al, 2013). Our correlations could also be affected by the numerous synergist muscles potentially contributing to trunk extensor and flexor torque output.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, when performed in adequate conditions (i.e., with sufficient learning) (Urzica et al, 2007), training programs aiming at improving trunk muscle strength could also reduce the disability level resulting from back pain (Keller et al, 2008), which is the most common pathology in the general population and constitutes a major public health issue (Schaafsma et al, 2013). In the same way, a strong and stable trunk facilitates the transfer of the forces generated by the upper and lower limb muscles (Kubo et al, 2011), thus contributing to athletic performance in different sports (Kubo et al, 2011;Tanaka et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…relates with the throwing performance [16]. These findings tempt us to assume that for golf players as well, having greater trunk muscle volume may be advantageous for achieving better golf performance.…”
Section: Introductionmentioning
confidence: 96%
“…Miyatani et al [ 23 ] reported the magnitude of SM mass required for preventing lifestyle-related diseases in Japanese women. Again, SMV is also a major determinant of muscle strength capability [ 8 , 35 ] and/or throwing performance [ 35 ] . Magnetic resonance imaging (MRI) is considered to be the most precise, reliable, and safe technique for determining SMV [ 22 ] .…”
mentioning
confidence: 99%